Toll-like receptors as therapeutic targets for autoimmune connective tissue diseases - Li, Jing; Wang, Xiaohui; Zhang, Fengchun; Yin, Hang (Pharmacology & therapeutics (Oxford), 2013)
Autoimmune connective tissue diseases (ACTDs) are a family of consistent systemic autoimmune inflammatory disorders, including systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), systemic sclerosis (SSc) and Sjögren's syndrome (SS). IL-1R-like receptors (TLRs) are located on various cellular membranes and sense exogenous and endogenous danger-associated molecular patterns (DAMPs) and pathogen-associated molecular patterns (PAMPs), playing a critical role in innate immune responses. During the past decade, the investigation of TLRs in inflammatory autoimmune diseases has been fruitful. In this report, we review the significant biochemical, physiological and pathological studies of the key functions of TLRs in ACTDs. Several proteins in the TLR signaling pathways (e.g., IKK-2 and MyD88) have been identified as potential therapeutic targets for the treatment of ACTDs. Antibodies, oligodeoxyribonucleotides (ODNs) and small molecular inhibitors (SMIs) have been tested to modulate TLR signaling. Some drug-like SMIs of TLR signaling, such as RDP58, ST2825, ML120B and PHA-408, have demonstrated remarkable potential, with promising safety and efficacy profiles, which should warrant further clinical investigation. Nonetheless, one should bear in mind that all TLRs exert both protective and pathogenic functions; the function of TLR4 in inflammatory bowel disease represents such an example. Therefore, an important aspect of TLR modulator development involves the identification of a balance between the suppression of disease-inducing inflammation, while retaining the beneficiary host immune response.